2022
DOI: 10.1093/toxsci/kfac108
|View full text |Cite
|
Sign up to set email alerts
|

Predicting human cardiac QT alterations and pro-arrhythmic effects of compounds with a 3D beating heart-on-chip platform

Abstract: Determining the potential cardiotoxicity and pro-arrhythmic effects of drug candidates remains one of the most relevant issues in the drug development pipeline. New methods enabling to perform more representative pre-clinical in vitro studies by exploiting induced pluripotent stem cell-derived cardiomyocytes (iPSC-CM) are under investigation to increase the translational power of the outcomes. Here we present a pharmacological campaign conducted to evaluate the drug-induced QT alterations and arrhythmic events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Such result would reinforce the interest in using patient-specific hiPSC-CMs for precision medicine. Our work supports previous studies on the development of hiPSC-based screening assays for testing individual drug reactions [ 55 57 ]. Altogether, they provide evidence that patient-specific hiPSC-CMs are a pertinent tool for drug screening and personalized medicine.…”
Section: Discussionsupporting
confidence: 90%
“…Such result would reinforce the interest in using patient-specific hiPSC-CMs for precision medicine. Our work supports previous studies on the development of hiPSC-based screening assays for testing individual drug reactions [ 55 57 ]. Altogether, they provide evidence that patient-specific hiPSC-CMs are a pertinent tool for drug screening and personalized medicine.…”
Section: Discussionsupporting
confidence: 90%
“…Both uHeart and uKnee models were successfully exploited for testing the effects of well-known drugs and innovative compounds. 56 The integration of beating OoCs, powered by uBeat, in a 3-D mechanical microenvironment resulted in OoC models with enhanced functionality and resemblance to pathological states. Beating OoCs are highly versatile and applicable to any organ in which mechanical stimulation exerts a pathophysiological state, representing new powerful tools for in vitro drug screening and disease modelling (Figure 2).…”
Section: Session 3: Alternative Models For Drug Treatmentmentioning
confidence: 99%
“…Lee at al showed that addition of a contractility assay (impedance measurement) into the evaluation of cardiotoxicity provides/allows more mechanistic insights on the drug effect [72]. As discussed above, 3D heart-on-a-chip models are also being tested, holding promise for even better prediction of cardiotoxic and pro-arrhythmic drug effects as they better recapitulated the clinical effects compared to 2D iPSC-CM models as they present occasionally with arrhythmias that are not reported in adult cardiomyocytes [73,74]. Regarding inherited cardiac arrhythmias, variable expressivity is a known characteristic, with many individuals who carry pathogenic variants remaining asymptomatic throughout life.…”
Section: Cardiotoxicity Screeningmentioning
confidence: 99%